Evidence on finance and economic growth - Alexander Popov (European Central Bank (ECB), 2017)
This paper reviews and appraises the body of empirical research on the association between .nancial markets and economic growth that has accumulated over the past quarter-century. The bulk of the historical evidence suggests that financial development affects economic growth in a positive, monotonic way, yet recent research endeavors have provided useful and important qualifications of this conventional wisdom. Moreover, the proliferation of micro-level datasets has enabled researchers to study more precise links between theory and measurement. The paper highlights the mechanisms through which financial markets benefit society, as well as the channels through which finance can slow down long-term growth.
Keywords: O4; G1; 330; financial markets; growth